Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.3389/fgene.2013.00159
|View full text |Cite
|
Sign up to set email alerts
|

Sarcopenia and piscines: the case for indeterminate-growing fish as unique genetic model organisms in aging and longevity research

Abstract: Sarcopenia and dynapenia pose significant problems for the aged, especially as life expectancy rises in developed countries. Current therapies are marginally efficacious at best, and barriers to breakthroughs in treatment may result from currently employed model organisms. Here, we argue that the use of indeterminate-growing teleost fish in skeletal muscle aging research may lead to therapeutic advancements not possible with current mammalian models. Evidence from a comparative approach utilizing the subfamily… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 78 publications
0
13
0
Order By: Relevance
“…Such an increase in pax7 expression during the myogenic progression to myotubes has been documented in the closely related species Salmo salar (Bower and Johnston 2010). Similarly, we recently demonstrated that expression of pax3 (another marker of MSCs in mammals) increases during a similar myogenic progression to myotubes in the indeterminately growing giant danio ( Devario aequipinnatus ) (Froehlich et al 2013). In mammalian myogenic cell cultures, pax7 is not expressed in differentiated myotubes, but is maintained in a smaller accompanying population of undifferentiated cells that stops proliferating and returns to a non-proliferating state reminiscent of the quiescent reserve MSCs, which can then reenter the cell cycle, proliferate, and differentiate (Kitzmann et al 1998, Yoshida et al 1998).…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…Such an increase in pax7 expression during the myogenic progression to myotubes has been documented in the closely related species Salmo salar (Bower and Johnston 2010). Similarly, we recently demonstrated that expression of pax3 (another marker of MSCs in mammals) increases during a similar myogenic progression to myotubes in the indeterminately growing giant danio ( Devario aequipinnatus ) (Froehlich et al 2013). In mammalian myogenic cell cultures, pax7 is not expressed in differentiated myotubes, but is maintained in a smaller accompanying population of undifferentiated cells that stops proliferating and returns to a non-proliferating state reminiscent of the quiescent reserve MSCs, which can then reenter the cell cycle, proliferate, and differentiate (Kitzmann et al 1998, Yoshida et al 1998).…”
Section: Discussionmentioning
confidence: 73%
“…Interestingly, an “unexpected” increase of pax7 expression (a well-accepted marker of quiescent MSCs in mammals) in culture of MSCs under differentiation into myotubes has been documented in a closely related species ( Salmo salar ), possibly reflecting the production of “quiescent reserve cells” (Bower and Johnston 2010). Likewise, we recently demonstrated that MSCs from the indeterminately growing giant danio ( Devario aequipinnatus ) in culture gradually increase pax3 expression (another marker of quiescent MSCs in mammals) during a similar progression to myotubes (Froehlich et al 2013). These data support the hypothesis that the induced expression of these specific paired-box transcription factors (pax3/7) during the culture of MSCs is a common feature of indeterminate growing species and could indicate a high self-renewal of MSCs, a process needed for these cells to continuously contribute to hyperplasia and/or hypertrophy during the lifespan of these fishes (Froehlich et al 2013).…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Rainbow trout exhibit indeterminate growth potential as they have the ability increase both body length and muscle mass throughout adulthood (Johnston et al, 2011). A physiological mechanism unique to indeterminate growers is the ability to maintain a population of myogenic precursor cells with proliferative capacity that then differentiate into myotubes or contribute to nuclear accretion (Mommsen, 2001; Froehlich et al, 2013). Therefore, the continued ability for hyperplasia and hypertrophy in skeletal muscle contributes to the indeterminate growth phenotype (Johnston et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…One group of fish whose growth patterns have been widely studied is the teleost. Teleost are bony fish that are marked by their indeterminate growth and phenotypic plasticity (Froehlich et al, 2013;Johnston et al, 2011). Teleost fish are also known for their great capacity for aerobic, sustained swimming, and anaerobic, burst swimming.…”
Section: Introductionmentioning
confidence: 99%